2-Pyrrolecarbaldiminato–Cu(ii) complex catalyzed three-component 1, 3-dipolar cycloaddition for 1, 4-disubstituted 1, 2, 3-triazoles synthesis in water at room temperature. Issue 9 (23rd December 2014) - Zhou, Changjian; Zhang, Jie; Liu, Ping; Xie, Jianwei; Dai, Bin
Abstract : 2-Pyrrolecarbaldiminato–Cu(ii ) complexes were first established as efficient catalyst for 1, 4-disubstituted 1, 2, 3-triazoles synthesis under green and mild reaction conditions. Abstract : 2-Pyrrolecarbaldiminato–Cu(ii ) complexes were established as efficient catalysts for the three-component 1, 3-dipolar cycloaddition reaction of benzyl halides and sodium azide with terminal alkynes in water at room temperature, and several regioselective 1, 4-disubstituted 1, 2, 3-triazoles have been synthesized under the reaction conditions in 55–97% yields.